LINGUSITIC ANALYSIS OF GENERATIVE ARTIFICIAL INTELLEGENCE GENERETED TEXTS - Solidjonov, Dilyorjon (University Research Base, 2024)
The linguistic analysis of AI-generated texts reveals critical insights into the syntactic, semantic, and pragmatic capacities of generative artificial intelligence. This study examines the capabilities and limitations of AI models, focusing on their ability to produce naturalistic text in English and Uzbek. While AI often achieves impressive surface-level accuracy, it struggles with deeper linguistic nuances, such as idiomatic expressions, cultural context, and flexible grammatical structures. The findings highlight the disparities in performance across languages, underscoring the need for more equitable representation of underrepresented languages in AI training datasets. Additionally, the study explores implications for linguistic theory, practical applications, and future research directions in enhancing AI's adaptability to diverse linguistic landscapes. Ultimately, this analysis contributes to a deeper understanding of the intersection between language and technology, offering pathways for more inclusive and context-aware AI development.